Efektifitas Penerapan Self Efikasi Terhadap Profil Lipid Pada Penderita Hiperlipidemia - Abdul Herman Syah Thalib; Elly Lilianty Sjattar; Syahrul Syahrul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Hyperlipidemia is one of the risk factors for atherosclerosis, which can cause coronary heart disease and stroke. To prevent this from happening, it is essential to detect early the level of lipid profile in human blood which includes Total Cholesterol (C-Total), High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), and Triglycerides (TG). Furthermore, one of the ways to control the cholesterol levels is by applying self-efficacy. In this respect, self-efficacy assessment was carried out by using a questionnaire called the Exercise Self-Efficacy Scale (ESES) and the Cardiac Diet Self-Efficacy Scale (CDSES). The purpose of this literature review is to describe the effectiveness of self-efficacy on lipid profile in hyperlipidemic patients.Method: The literature review was gained from Pubmed, ProQuest, Google Scholar, and secondary literature search.Result: There were 37 articles identified and published from 2012-2018. Of the 37 articles, there were 7 articles that met the inclusion criteria. As a result, these seven articles show that the application of self-efficacy is able to improve the patients' self-confidence.Conclusion: The application of self-efficacy is able to help nurses increase the patients' self-confidence. In addition, self-efficacy assessment can be performed by using self-efficacy instruments in an effort to control the lipid profile of hyperlipidemic patients.Keywords: Self-efficacy, Lipid Profile, Hyperlipidemia